2015
DOI: 10.1186/s12883-015-0460-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the brief international cognitive assessment for multiple sclerosis and the brief repeatable battery in multiple sclerosis patients

Abstract: BackgroundRecently, a Brief International Cognitive Assessment for Multiple Sclerosis (BICAMS) has been developed as an international and standardized brief cognitive test, which is easily performed in everyday clinical practice for neuropsychological assessment in multiple sclerosis (MS). However, we need to gather more information about this tool compared to other neuropsychological batteries. The aim of our study is to compare the performance of BICAMS and Brief Repeatable Battery (BRB) in MS subjects.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 18 publications
5
23
0
1
Order By: Relevance
“…The score obtained by patients with MS in the SDMT in previous publications ranges from 34.9 to 56.3 with a mean of 43.5 (mean SD = 14.1) 3,7,10,13,20,21,22,23,24 , close to our result of 48.5 (SD = 14.9). Importantly, in the study that showed the lower score 7 , the population assessed was of older patients (mean age 61.8 years) and with longer duration of disease (mean 34.5 years) compared to ours, which possibly influenced its results.…”
supporting
confidence: 89%
See 4 more Smart Citations
“…The score obtained by patients with MS in the SDMT in previous publications ranges from 34.9 to 56.3 with a mean of 43.5 (mean SD = 14.1) 3,7,10,13,20,21,22,23,24 , close to our result of 48.5 (SD = 14.9). Importantly, in the study that showed the lower score 7 , the population assessed was of older patients (mean age 61.8 years) and with longer duration of disease (mean 34.5 years) compared to ours, which possibly influenced its results.…”
supporting
confidence: 89%
“…The patients had a mean of 52 points, very close to our 48.2. In other studies, this findings was similar, ranging from 42 to 51.6 points 12,22,23,24,25 . Only one paper 13 showed a significant discrepancy, with a mean in the CVLT of 64 in patients with MS 2 .…”
supporting
confidence: 86%
See 3 more Smart Citations